A Convergence of Forces: Disability Rights and The Founding Moment of the Ghana Society of the Physically Disabled, 1980–81 - Grischow, Jeff; Mfoafo-M’Carthy, Magnus; Naami, Augustina (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
This article analyzes the postcolonial history of disability rights in Ghana by focusing on the founding and early expansion of the Ghana Society of the Physically Disabled (GSPD) in Kumasi in 1980. The GSPD’s founding moment occurred later than such similar disabled people’s organizations as the Ghana Association of the Blind and the Ghana National Association of the Deaf, which were created in the 1960s. We suggest several reasons for rise of the GSPD and the timing of its creation by focusing on a convergence of forces around 1980, as well as the longer history of disability in Ghana. More specifically, the article analyzes the GSPD’s founding moment through the lens of grassroots organizing and civil society in a particularly Ghanaian context. We also assess the connections between the GSPD’s first-generation organizers, government ministries, and international disability NGOs (especially Nordic organizations). As such, the article situates the founding of the GSPD within larger national and global disability initiatives as well as the history of disability in Ghana. Due to a lack of archival materials, our analysis is based on field interviews supplemented by written sources where possible.